Transcriptome Changes of Mycobacterium marinum in the Process of Resuscitation From Hypoxia-Induced Dormancy - Jiang, Jun; Lin, Chen; Zhang, Junli; Wang, Yuchen; Shen, Lifang; Yang, Kunpeng; Xiao, Wenxuan; Li, Yao; Zhang, Lu; Liu, Jun (Frontiers in Genetics, 2020)
Nearly one-third of the world’s population is latently infected with Mycobacterium tuberculosis (M. tb), which represents a huge disease reservoir for reactivation and a major obstacle for effective control of tuberculosis. During latent infection, M. tb is thought to enter nonreplicative dormant states by virtue of response to hypoxia and nutrient deprived conditions. Knowledge of the genetic programs used to facilitate entry into and exit from the nonreplicative dormant states remains incomplete. In this study, we examined the transcriptional changes of Mycobacterium marinum (M. marinum), a pathogenic mycobacterial species closely related to M. tb, at different stages of resuscitation from hypoxia-induced dormancy. RNA-seq analyses were performed on M. marinum cultures recovered at multiple time points after resuscitation. Differentially expressed genes (DEGs) at each time period were identified and analyzed. Co-expression networks of transcription factors and DEGs in each period were constructed. In addition, we performed weighted gene co-expression network analysis (WGCNA) to all genes and obtained 12 distinct gene modules. Collectively, these data provide valuable insight into the transcriptome changes of M. marinum upon resuscitation, as well as gene module function of the bacteria during active metabolism and growth.